Introduction to DC motors for engineering students based on laboratory experiments - Pinto, Vítor H. (2020)
Since DC Motors are common components in engineering projects that involve process control, it is necessary for any student in this area to understand their concepts, construction and applications. This paper focuses on a series of Laboratory Experiments that were carried out in an Entry Level Unit of the Integrated Master Degree in Electrical and Computers Engineering of the Faculty of Engineering of the University of Porto, named Project FEUP. In this class, mandatory for all students, they learn to how use these motors, from basic concepts to the estimation modeling. The paper presents the developed kits that students use, the simplified model and examples of the experiments performed in some classes.